Facilitators and barriers to implementing electronic referral and/or consultation systems: a qualitative study of 16 health organizations. Issue 1 (June 2015) - Tuot, Delphine; Leeds, Kiren; Murphy, Elizabeth; Sarkar, Urmimala; Lyles, Courtney; Mekonnen, Tekeshe; Chen, Alice
Abstract Background Access to specialty care remains a challenge for primary care providers and patients. Implementation of electronic referral and/or consultation (eCR) systems provides an opportunity for innovations in the delivery of specialty care. We conducted key informant interviews to identify drivers, facilitators, barriers and evaluation metrics of diverse eCR systems to inform widespread implementation of this model of specialty care delivery. Methods Interviews were conducted with leaders of 16 diverse health care delivery organizations between January 2013 and April 2014. A limited snowball sampling approach was used for recruitment. Content analysis was used to examine key informant interview transcripts. Results Electronic referral systems, which provide referral management and triage by specialists, were developed to enhance tracking and operational efficiency. Electronic consultation systems, which encourage bi-directional communication between primary care and specialist providers facilitating longitudinal virtual co-management, were developed to improve access to specialty expertise. Integrated eCR systems leverage both functionalities to enhance the delivery of coordinated, specialty care at the population level. Elements of successful eCR system implementation included executive and clinician leadership, established funding models for specialist clinician reimbursement, and a commitment to optimizing clinician workflows. Conclusions eCR systems have great potential to streamline access to and enhance the coordination of specialty care delivery. While different eCR models help solve different organizational challenges, all require institutional investments for successful implementation, such as funding for program management, leadership and clinician incentives.